New Perspectives on Internationalization and Competitiveness: Integrating Economics, Innovation and Higher Education - Ullberg, Eskil (Springer, 2016)
​This volume showcases contributions from leading academics, educators and policymakers derived from two workshops hosted by the Interdisciplinary Center for Economic Science (ICES) at George Mason University on internationalization and competitiveness. It aims to present key areas of current research and to identify basic problems within the field to promote further discussion and research. This book is organized into two sections, focusing on: science and economics and innovation policy and its measurement, with an underlying emphasis on exploring connections across disciplines and across research, practice and policy.